2017
DOI: 10.1016/j.cct.2017.05.011
|View full text |Cite
|
Sign up to set email alerts
|

MortalitY in caRdIAc surgery (MYRIAD): A randomizeD controlled trial of volatile anesthetics. Rationale and design

Abstract: The trial will determine whether the simple intervention of adding a volatile anesthetic, an intervention that can be implemented by all anesthesiologists, can improve one-year survival in patients undergoing coronary artery bypass graft surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 30 publications
0
10
0
2
Order By: Relevance
“…Interim analyses were planned after enrollment of 25%, 50%, and 75% of the planned number of patients. 23,32,33 The planned approach to statistical analysis was published previously. 23 Primary analyses were performed according to the intention-to-treat principle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interim analyses were planned after enrollment of 25%, 50%, and 75% of the planned number of patients. 23,32,33 The planned approach to statistical analysis was published previously. 23 Primary analyses were performed according to the intention-to-treat principle.…”
Section: Discussionmentioning
confidence: 99%
“…Details of the rationale, design, and statistical plan have been published previously. 23 The MYRIAD trial was endorsed by the European Association of Cardiothoracic Anesthesiologists and was funded by the Italian Ministry of Health. The funding body had no role in the design of the trial, the collection and analysis of the data, or the writing of the manuscript or in the decision to submit the manuscript for publication.…”
Section: Trial Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Several factors may have contributed to these results, including an actual low incidence of severe perioperative myocardial ischemia in the current clinical practice of cardiac surgery, and, although the MYRIAD study clearly has shown that volatile anesthetics are not a magic bullet, its findings probably did not allow for the definite exclusion of any beneficial effect of volatile anesthetics in cardiac surgery. 103 The pragmatic design of the MYRIAD study 55,104 left the attending anesthesiologist free to choose the volatile anesthetic to use, its doses and duration of administration, the phases of surgery in which to administer it, and whether simultaneously to use any intravenous agent (eg, opioids, propofol, midazolam). However, APC may be dose dependent and related to the timing and duration of administration and may be more pronounced with some agents over others, although the largest direct comparison between 2 different volatile anesthetics 105 and the aforementioned Bayesian network meta-analysis 95 did not suggest a different effect on clinically relevant outcomes among different volatile anesthetics; further, other drugs may enhance (eg, opioids) or counteract (eg, propofol) the cardioprotective action of volatile anesthetics (see Table 2).…”
Section: General Anesthesia and Outcomementioning
confidence: 99%
“…Los anestésicos volátiles o inhalatorios, frente al propofol, han demostrado preservar mejor la función cardiaca tras la CEC (menor liberación de troponinas), asociarse a menor mortalidad y a menos complicaciones pulmonares [216][217][218][219] . Sin embargo, el ensayo MYRIAD concluye que no existe una reducción significativa de la mortalidad a los 30 días ni al año en pacientes sometidos a cirugía electiva de revascularización coronaria 220 . Por ello, varias guías clínicas sugieren que esos resultados deberían aplicarse a la anestesia cardiaca 74,221 .…”
Section: Mantenimientounclassified